Comparison and culturing different types of cells from fresh breast milk with different culture medium - Tang, Chuanqing; Zhou, Qi; Lu, Chunmei; Xiong, Man; Lee, Shookim (Pediatric Medicine, 2019)
Background: To investigate the properties of breast milk cells at different stages and culture different types of cells from fresh breast milk. Methods: Cell concentration and viability were analyzed after being isolated from fresh breast milk. Cell properties were tested by flow cytometry with different cell surface markers. Different types of breast milk cells were cultured with different medium. After being purified, the cells were identified by flow cytometry and immunofluorescence. Results: The concentration of breast milk cells decreased with lactation time. The viability of breast milk cells decreased gradually in both colostrum and transitional milk (C and T milk) group and mature milk group, and there was no significant difference in two groups over time. The expression levels of different cell surface markers were higher in C and T milk than mature milk. Using three different culturing media, we could get different types of cells including immune cells, mammary epithelial cells (MECs), mesenchymal stem cells (MSCs) and breast milk stem cells (BSCs) with different efficiency between C and T milk and mature milk. Conclusions: C and T milk contains more cells than mature milk, especially immunocytes. It is feasible to culture MECs with F medium, MSCs with M medium or F medium, and BSCs with CM medium.